Competitive Human Capital and Football Club’s Performance: Case of the English Premier League - Mysaka, Hanna; Derun, Ivan; Holovanenko, Mykola (Ekonomika, 2026)
The objective of this study is to examine the interrelation between competitive human capital (CHC) and a professional football club’s (PFC) sports performance (SP) and business performance (BP). The research methodology is based on a seemingly unrelated regressions (SUR) model with panel data. Empirical results are tested on data of the 41 PFCs in the English Premier League (EPL) for the period of 2008–2023. We find that CHC has a positive impact on SP and on the intensity of stream of broadcasting revenue (BR) as the main driver of PFC revenue, but it has a negative impact on BP. Additionally, the results indicate that the media interest in PFC has a limited financial impact, and the financial aspects of a transfer policy are secondary to the club’s ability to generate revenue, while CHC expenses reduce PFCs’ business efficiency, profitability, and liquidity. PFCs should focus on balancing between SP and BP by optimizing transfer and wage expenditures. Furthermore, given UEFA’s requirements for settling overdue payables, clubs should take measures to increase liquidity. This paper contributes to the field by applying a SUR model in the context of SP and BP of PFC as a for-profit entity (with an emphasis on the influence of CHC on the intensity of stream of BR), which is a relatively novel research avenue. It can act as a foundation for studying the impact of CHC parameters on PFCs’ sports, business, and financial performance as a virtuous cycle of performance.
Keywords: broadcasting revenue; business performance; competitive human capital; professional football club; sports performance